MODEL PENDIDIKAN KARAKTER MULTIKULTURAL (STUDI KASUS DI PP. NURUL HIDAYAH KONCER JATIAN TENGGARANG BONDOWOSO) - Salam, Miftahus (International Conference on Humanity Education and Society (ICHES), 2024)
Based on these considerations, this research takes the theme of character education and is formulated in the title: "MODEL OF CHARACTER EDUCATION (Case study of the implementation of character education at Nurul Hidayah Koncer Kidul Tenggarang Bondowoso Islamic Boarding School)". The focus of this research is to find out (1) how is the process of character education at the Nurul Hidayah Koncer Jatian Bondowoso Islamic Boarding School? (2) how are the indicators of the successful implementation of character education at the Nurul Hidayah Koncer Jatian Bondowoso Islamic Boarding School.The form of this research is descriptive qualitative. Data collection was carried out by direct observation, in-depth interviews and document recording. Data validation is done by triangulation. The analysis used is an interactive analysis model, namely data collection, data reduction, data presentation and conclusion drawing. The results of this study concluded that (1) the process of implementing character education at Pondok Pesantren Nurul Hidayah Koncer Jatian Tenggarang Bondowoso is through the learning curriculum (there are lessons that teach morals or manners), extracurricular activities, school culture, and teacher exemplary. Another pattern for developing character education in PP. Nurul Hidayah with a dormitory model (boarding school). (2) Teachers' and students' perceptions of character education will influence its implementation at school. Teachers and students' perceptions of character education that emerged in PP. Nurul Hidayah emphasizes Islamic character. This perception is based on the ideology applied in schools and Madrasahs. (3) The success of character education at school and in Madrasah can be seen from the actualization of students in the form of attitudes or actions seen in students. Actualization that appears in students at PP. Nurul Hidayah includes tolerance, religion, discipline, honesty, creativity, cooperation, communicative, caring, independence, love for the country and responsibility. Nurul Hidayah boarding school has more diverse values, one of which is patience, simplicity which is seen in daily activities.